Money Politics on General Election 2019 - Umagapi, Juniar Laraswanda (Universitas Negeri Semarang, 2023)
Money politics must be connected to the constellation of elections in Indonesia. There is no election without money and politics. This research aims to describe real-world examples of money politics during the 2019 election, cases of money politics that occurred in society and impacted democracy, and future recommendations for the government. Gellner & Waterbury, Patrons and Clients in the Mediterranean Societies,” said money politics exists in a patron-client society when groups in power or with certain privileges give money or other gifts in return for the loyalty of their followers (clients). The money-politics system is not a system that only surrounds elections. Money politics started to happen even before the election took place. Furthermore, it is essential to know the sources of money for state officials. This study uses library research to elaborate on various kinds of literature in the form of books, journals, and other literature relevant to the article’s theme and interviews. This article describes cases of money politics that occurred in the 2019 simultaneous elections. The culture of money politics that occurred and the legal loopholes in money politics became obstacles to enforcing money politics cases. Lastly, it is a conclusion if money politics is direct or does not impact the election result.